2000
DOI: 10.1002/pen.11248
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the mechanical properties of chitosan films by the addition of poly(ethylene oxide)

Abstract: The mechanical properties of films prepared from mixed acetic acid aqueous solutions of chitosan (Mw = 400,000; Mw/Mn = 3.8) and poly(ethylene oxide) (PEO) (viscosity average molecular weight of 200,000 or 600,000) were determined. A chitosan:PEO weight ratio of 10:2 improved the mechanical properties compared with pure chitosan films. The improvement of the mechanical properties correlated with a small reduction of the correlation length measured by small‐angle neutron scattering (SANS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 11 publications
1
34
0
Order By: Relevance
“…55 Crosslinking is used to enhance mechanical strength and chemical stability, to control aqueous permeability and solubility of the hydrogels, and to decrease the aqueous swelling features of chitosan-based materials. [56][57][58][59][60][61] Crosslinking of the chitosan component with genipin enabled the creation of hydrogels with varying substrate stiffness, without changing the polysaccharide constituents. Results demonstrated that material properties (gel stiffness) can be leveraged to induce osteoblast differentiation in 2D culture as an alternative to biochemical cues such as soluble supplements, immobilized biomolecules and vectors, which are often expensive, labile and potentially carcinogenic.…”
Section: Discussionmentioning
confidence: 99%
“…55 Crosslinking is used to enhance mechanical strength and chemical stability, to control aqueous permeability and solubility of the hydrogels, and to decrease the aqueous swelling features of chitosan-based materials. [56][57][58][59][60][61] Crosslinking of the chitosan component with genipin enabled the creation of hydrogels with varying substrate stiffness, without changing the polysaccharide constituents. Results demonstrated that material properties (gel stiffness) can be leveraged to induce osteoblast differentiation in 2D culture as an alternative to biochemical cues such as soluble supplements, immobilized biomolecules and vectors, which are often expensive, labile and potentially carcinogenic.…”
Section: Discussionmentioning
confidence: 99%
“…From this point of view, a research interest has been placed on blending of CS with poly(ethylene oxide) (PEO). [1][2][3][4][5] CS/PEO blends exhibit the improvement in thermal, mechanical and electrical properties because of the specific interactions between the amine and hydroxyl groups of CS and the ether groups of PEO [1][2][3][4] , as naturally expected from their chemical structures shown later in Fig.1. The CS/PEO blends have a potential applicability as a matrix in the solid polymer electrolyte [6][7][8] , because both CS and PEO can dissolve salts to exhibit ionic conductivity.…”
Section: Introductionmentioning
confidence: 91%
“…Residue of PEO in animal tissue normally induced few immune responses owing to its extremely low toxicity. 28,29 Moreover, composites of PEO in biomimetic scaffolds favored the formation of neocartilage. 30 Recently, influences of the composition on porosity and mechanical strength of PEO/chitin/chitosan scaffolds and applications of the ternary scaffolds to cartilage tissue engineering were investigated.…”
Section: Introductionmentioning
confidence: 99%